2022
DOI: 10.21608/ejhm.2022.246927
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Bupivacaine with Dexamethasone versus Bupivacaine Alone for Pain Relief after Laparoscopic Bariatric Surgeries: A Randomized Controlled Trial

Abstract: Background: Pain after laparoscopic bariatric surgeries has negative effects on patients' recovery. Objective: To evaluate efficacy and safety of adding intraperitoneal dexamethasone to bupivacaine for postoperative pain relief after laparoscopic bariatric surgeries. Patients and Methods: Sixty patients were randomly allocated into 3 groups as follows: Group B (n=20): bupivacaine 100 ml 0.25% + 5 ml normal saline. Group BD4 (n=20): bupivacaine 100 ml 0.25% + 4 mg dexamethasone (1 ml) + saline 4 ml, and Group B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The total dose of Nalbuphine in the 1 st 24 hrs was significantly lower in in group III compared to group I and group II (P<0.001, 0.001) and was significantly lower in group II compared to group I (P=0.003). Nasr et al [14] performed a randomized clinical trial to evaluate efficacy and safety of adding intraperitoneal dexamethasone to bupivacaine for postoperative pain relief after laparoscopic bariatric surgeries. [11] performed a randomized prospective trial on a total of 100 patients scheduled for laparoscopic cholecystectomy (LC) who were randomized into two equal groups, group RD received 0.2% ropivacaine 30 ml plus 8 mg dexamethasone, and group RS received 0.2% ropivacaine 30 ml plus 2 ml normal saline intraperitoneally to evaluate the intraperitoneal ropivacaine with dexamethasone versus ropivacaine alone for pain relief after LC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total dose of Nalbuphine in the 1 st 24 hrs was significantly lower in in group III compared to group I and group II (P<0.001, 0.001) and was significantly lower in group II compared to group I (P=0.003). Nasr et al [14] performed a randomized clinical trial to evaluate efficacy and safety of adding intraperitoneal dexamethasone to bupivacaine for postoperative pain relief after laparoscopic bariatric surgeries. [11] performed a randomized prospective trial on a total of 100 patients scheduled for laparoscopic cholecystectomy (LC) who were randomized into two equal groups, group RD received 0.2% ropivacaine 30 ml plus 8 mg dexamethasone, and group RS received 0.2% ropivacaine 30 ml plus 2 ml normal saline intraperitoneally to evaluate the intraperitoneal ropivacaine with dexamethasone versus ropivacaine alone for pain relief after LC.…”
Section: Discussionmentioning
confidence: 99%
“…in Group B (Bupivacaine group) and versus (7.4 ± 0.55 hr.) in Group BD4 (Bupivacaine+ 8 mg dexamethasone group) (P<0.001), according to a previous study [14] . Based on the following considerations: 0.05 α error and 90% power of the study.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…This finding aligns with the observation made by Nasr et al . [ 13 ], who reported that patients receiving intra-peritoneal bupivacaine with 8 mg dexamethasone had a significantly longer duration of analgesia 9.2 h (0.14) as compared to bupivacaine alone 6.1 h (0.19) following laparoscopic bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the total rescue analgesic dose needed was significantly less in the BD group. Similar findings were noted by Nasr et al .,[ 13 ] who reported that patients receiving intra-peritoneal bupivacaine with dexamethasone consumed significantly less rescue analgesic 3.4 mg (2.8) compared to bupivacaine alone 15.2 mg (7.5) with P < 0.001 following laparoscopic bariatric surgery. Similarly, Srivastava et al .…”
Section: Discussionmentioning
confidence: 99%